2014
DOI: 10.1080/13573322.2014.947566
|View full text |Cite
|
Sign up to set email alerts
|

HPE in Aotearoa New Zealand: the reconfiguration of policy and pedagogic relations and privatisation of curriculum and pedagogy

Abstract: This paper centres on research that investigated the contemporary policy, curriculum and pedagogical landscape of Health and Physical Education (HPE) in Aotearoa New Zealand, in the light of increasing impressions that provision was moving to an 'open market' situation. Publicly available information sourced via the Internet was used to examine the public and privately funded initiatives, programmes and resources targeted towards the provision of HPE across all phases of education. The data arising revealed an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 17 publications
1
11
0
Order By: Relevance
“…Funding decisions have played a key role in raising the profile of sport and health agents/agencies in this field, to the point that the Ministry of Education has been seen as inactive (Petrie & lisahunter, 2011), with its influence in the field superseded by sporting agencies in particular. As discussed in more detail elsewhere (Petrie et al, 2014;Penney et al, 2015) our data clearly demonstrated that this change in the configuration of the Official Recontextualizing Field was being mirrored in the Pedagogic Recontextualizing Field. In both fields, the impression was that significant displacement of educational agencies was occurring.…”
Section: And the Dissolution Of Key Policy And Pedagogic Boundariessupporting
confidence: 69%
See 2 more Smart Citations
“…Funding decisions have played a key role in raising the profile of sport and health agents/agencies in this field, to the point that the Ministry of Education has been seen as inactive (Petrie & lisahunter, 2011), with its influence in the field superseded by sporting agencies in particular. As discussed in more detail elsewhere (Petrie et al, 2014;Penney et al, 2015) our data clearly demonstrated that this change in the configuration of the Official Recontextualizing Field was being mirrored in the Pedagogic Recontextualizing Field. In both fields, the impression was that significant displacement of educational agencies was occurring.…”
Section: And the Dissolution Of Key Policy And Pedagogic Boundariessupporting
confidence: 69%
“…The first illustration comes from research in Aotearoa New Zealand, and a project that I undertook in collaboration with Kirsten Petrie and Sam Fellows (Petrie, Penney, & Fellows, 2014;Penney, Petrie, & Fellows, 2015). The project arose in response to our growing awareness of the growth in socalled external providers offering resources, services and 'support' to schools and teachers, that was variously directed towards their provision of HPE, physical education, health, physical activity and/or sport programmes within or outside of curriculum time.…”
Section: Policy Contexts Problems and Magic In Physical Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…Penny et al (2013) examination of physical education and sport in primary schools was, for example, restricted to six schools while Penny et al (2015), study looking at ''the public and privately funded initiatives, programmes and resources targeted towards the provision of HPE'' (p 42) was limited to an analysis of what was available on the internet.…”
Section: Introductionmentioning
confidence: 99%
“…Invariably this and other health messages espoused by the children reinforced the concept of corporeality. Research suggests that it was difficult and complex for some of the primary generalist teachers in the study to grasp and implement multiple health concepts and broader educational policies and initiatives simultaneously (Atkins, 2015;Penney, Petrie & Fellows, 2015;Petrie, 2012). Instead, a simplistic popular health discourse such as obesity was replicated and a pedagogy of healthism was adopted.…”
Section: Discussionmentioning
confidence: 99%